2010
DOI: 10.1063/1.3456729
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale domains in strained epitaxial BiFeO3 thin Films on LaSrAlO4 substrate

Abstract: BiFeO 3 thin films with various thicknesses were grown epitaxially on (001) LaSrAlO 4 single crystal substrates using pulsed laser deposition. High resolution x-ray diffraction measurements revealed that a tetragonal-like phase with c-lattice constant ~4.65 Å is stabilized by a large misfit strain. Besides, a rhombohedral-like phase with c-lattice constant ~3.99 Å was also detected at film thickness of ~50 nm and above to relieve large misfit strains. In-plane piezoelectric force microscopy studies showed clea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
82
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 24 publications
9
82
0
Order By: Relevance
“…As predicted from the crystallographic information, the ferroelectric domain structure does rotate by 45 ° in the stripe pattern. Th e phase at lower temperature has dense stripe domains with a typical domain width of ~ 50 nm along 〈 110 〉 c direction, which is consistent with the PFM images reported by Chen et al 23,25 ; whereas the higher temperature phase has much larger stripe domains, which are elongated along 〈 100 〉 c . Th is suggests that the domain walls at the higher temperature have a higher energy cost to be stabilized.…”
Section: Resultssupporting
confidence: 80%
“…As predicted from the crystallographic information, the ferroelectric domain structure does rotate by 45 ° in the stripe pattern. Th e phase at lower temperature has dense stripe domains with a typical domain width of ~ 50 nm along 〈 110 〉 c direction, which is consistent with the PFM images reported by Chen et al 23,25 ; whereas the higher temperature phase has much larger stripe domains, which are elongated along 〈 100 〉 c . Th is suggests that the domain walls at the higher temperature have a higher energy cost to be stabilized.…”
Section: Resultssupporting
confidence: 80%
“…Coexisting crystallographic phases have been observed in several inorganic perovskite materials of mixed [35][36][37] and pure [38][39][40] composition. For the latter case, it has been shown that the secondary phase can be stabilized through the effect of strain imposed on a thin film by the substrate 38,39 or through external pressure.…”
mentioning
confidence: 99%
“…Coexisting crystallographic phases have been observed in several inorganic perovskite materials of mixed [35][36][37] and pure [38][39][40] composition. For the latter case, it has been shown that the secondary phase can be stabilized through the effect of strain imposed on a thin film by the substrate 38,39 or through external pressure. 40 Despite the fact that CH 3 NH 3 PbI 3−x Cl x -films studied here were grown on an amorphous glass substrate, and hence any lattice-mismatch of the as-grown sample is ruled out, unequal thermal expansion and, more importantly, the spontaneous change of the in-plane lattice constants during the phase-transition 26 may well cause a significant amount of strain to the film.…”
mentioning
confidence: 99%
“…There values are close to the reported T and R structure parameters. 22,23 In order to further confirm the crystallographic orientation relationship between BFO and MgO substrate, pole figures were also recorded. As expected, Fig.1 The BFO/TiN/MgO structures were also examined by the cross-sectional STEM observations and the images are shown in Fig.2.…”
Section: Methodsmentioning
confidence: 99%